Analysis of Islamic Law in the Context of Lethal Injection for Terminated Patients in Indonesia - Syahriani, Fadilla; Ngardi, Valensius; Mulyani, Fini Fajri; Fismanelly, Fismanelly; Mardiati, Diana (IDRIS Darulfunun Institute, 2024)
This study delves into the examination of Islamic law within the framework of lethal injection for terminally ill patients in Indonesia. The research focuses on the ethical and legal dimensions surrounding the use of lethal injection as a method of administering end-of-life care for individuals facing terminal illnesses. Employing a comprehensive analysis of Islamic legal literature and scrutiny of Indonesia's legal provisions pertaining to the termination of patients, the study seeks to ascertain the compatibility of lethal injection with Islamic principles. The research adopts a comparative legal analysis approach, comparing the tenets of Islamic law with Indonesia's existing legal framework concerning end-of-life decisions. By exploring the perspectives of prominent Islamic scholars and jurists, the study aims to provide insights into the multifaceted nature of the debate surrounding lethal injection within the context of Islamic law. The findings of this analysis will contribute to the ongoing discourse on ethical considerations and religious perspectives regarding end-of-life care, with implications for Indonesia's healthcare policies and legal regulations in the realm of terminal patient care.